Fundamentals, principle and practice of purposeful Penalization model - mohammadali hajidehabadi; ehsan salimi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2020)
A review of criminal law clearly reveals that in Iran's legal system, there is no particular logic of penalization, and in these laws, many inappropriate penalties exist in terms of type, degree and inefficiency in achieving the goals. Cliché and irregular punishments not only result in failure to meet the goals of punishment, but leads to undesirable and adverse effects on the perpetrator. Determining the appropriate punishment and the optimum level of efficiency, is very complex issue and requires attention to many components. The present article, which Seeks to the identify purposeful penalization model, insists that the legislator must, in each crime, before any other issues should determine his "Main purpose" and choose the type of punishment according to that goal, and avoid from totalitarianism for acquisition of opposite objectives. Regarding the amount of punishment, the legislators should also consider the ease and advantages of committing a crime, the dark figure of crime, the commonness of crime and the relationship of crimes with each other, while at the same time, in line with the principle of individualizing punishment and increasing the positive effect of punishment, The judge must give more authority to determine the amount of punishment.